Protocatechuic acid attenuates brain edema and blood-brain barrier disruption after intracerebral hemorrhage in mice by promoting Nrf2/HO-1 pathway. Issue 18 (16th December 2020) - Xi, Zhiyu; Chen, Xiao; Xu, Canxin; Wang, Baofeng; Zhong, Zhihong; Sun, Qingfang; Sun, Yuhao; Bian, Liuguan
Abstract : The brain edema following intracerebral hemorrhage (ICH) plays a key role in the recovery process. Protocatechuic acid (PCA) has been proved possessing neuroprotection in ICH. Here we tried to explore its value in brain edema after ICH and reveal underlying mechanisms. ICH model was created in C57 mice using collagenase IV. PCA was injected intraperitoneally at 30 mg/kg every 24 h in PCA group. On day 3 after ICH, the water content of hemorrhagic ipsilateral hemisphere in PCA group was significantly reduced compared with vehicle group. AQP4, the main water channel, was remarkably decreased in PCA group. Additionally, ZO-1 and occludin expression were increased in PCA group. The bEnd.3 cells were cultured to understand the effect of PCA on the blood-brain barrier (BBB) integrity. Compare to hemin treated group, plus PCA enhanced the expression of HO-1 and Nrf2 nuclear translocation. Furtherly, the overexpression of HO-1, ZO-1, occludin, in the PCA treatment group was inhibited after knockdown of Nrf2. Taken together, our results proved PCA alleviated brain edema and BBB disruption in ICH by promoting the Nrf2/HO-1 signaling pathway.